Plan de negocios para la creación de una empresa productora y comercializadora de productos a base de jengibre - González Hermosa, Daniela Alejandra (2017)
Finca Asagtús, is a new and innovative company in the marmalade market. It seeks to deliver a new concept on how to care for health and relieve pain, through the consumption of natural ginger jelly, to people between the ages of 30 to 45 years residing in the city of Quito. The main reason for the initiative to create this product is the need to alleviate the pain of those suffering from rheumatism or pain of any kind, through the consumption of foods with natural healing properties. The implementation of an ingredient centrifugation technique, which allows the preservation of the natural properties of ginger, is the basis on which the company carries out its operations; that means, delivering ginger jam without losing the potential benefits of this root. Finca Asagtús, seeks to deliver a new way to consume ginger, which at the same time, allows creating a habit of health care and offers a more natural alternative to pain relief. Referring to the market research conducted, the findings of the same, were positive. Individuals, men and women, between the ages of 30 and 45, show a great disposition to the consumption of natural foods to take care of health. In conclusion, the ginger jam is very attractive for this segment of people who seek to take care of health and at the same time relieve pain through the consumption of ginger. On the other hand, the present project shows positive results in the financial analysis; so it is feasible to project it over a period of five years.